Repositioning Poetra Ardani Tempe Crispy Chips as Special Gift of Malang - Daru Redono (Jurnal VOK@SINDO, 2014)
Small Medium Enterprise (SME) is one of the country's economy supports .Some of the SME products are able to compete with other exported products. However, some may only survive in the local area and are less able to compete with others. This is the problem faced by producers of Tempe crispy chips, Poetra Ardani. The problem is caused by the absence of the product’s visual identity as a brand. As a result, the consumers are not aware of the product’s brand which then results in reducing the sale of the products. In addition, souvenir centers are mostly located in particular areas and the products mostly have similar visual identity even though the brands are different. This is why a brand might be less memorable and cannot establish an emotional connection with their customers. To solve these problems, repositioning needs to be done in which a brand gives different concept in consumers’ mind. With this differentiation method, a brand can explore what distinguishes between one brand and others. The differences of each brand are the ones that will be communicated continuously through visual media such as logos, packaging, promotion, gimmick in order to make the brands memorable for customers.